2016
DOI: 10.1080/13504509.2016.1232319
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of San Francisco’s planning standard for pedestrian wind comfort

Abstract: In 1985, San Francisco adopted a wind comfort standard in its Downtown Area Plan in response to increasing concerns about the city's downtown public open spaces becoming excessively windy. After 30 years of implementation, this study revisits the standard and examines its effectiveness in promoting pedestrian comfort. 701 valid samples were collected from 6 months of field study, which combined surveying pedestrians and on-site collection of microclimate data. Statistical analysis and an assessment using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Outdoor public spaces in these residential areas are not only a transition between the residential unit and urban space but also an important place for older people to interact with nature and engage in healthy daily behaviours. The quality of these spaces can significantly influence the wellness of older people [16][17][18]. Similar to the development of urban construction in Western developed countries, China has transitioned from an era of mass building to a stage of stock building regeneration [19].…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor public spaces in these residential areas are not only a transition between the residential unit and urban space but also an important place for older people to interact with nature and engage in healthy daily behaviours. The quality of these spaces can significantly influence the wellness of older people [16][17][18]. Similar to the development of urban construction in Western developed countries, China has transitioned from an era of mass building to a stage of stock building regeneration [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by physical symptoms, such as high body temperature, dry skin and a lack of sweating and neurological symptoms, such as irritation, dizziness and difficulty breathing (Kovats and Hajat, 2008). Heat stress is closely related to thermal comfort, a subjective evaluation index of residents' health and well-being (Singh et al, 2011) that is affected by environmental conditions, such as air temperature, wind level, solar radiation, humidity and personal factors, including metabolic rate and clothing insulation (Kim and Macdonald, 2017;Nicol, 2004). Recent studies have demonstrated that increased air temperature can not only lead to increased heat stress, but can also increase energy use for air-conditioning (Johansson and Emmanuel, 2006;Kim et al, 2018;Ndetto and Matzarakis, 2013Ng et al, 2012;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%